R&D policies and change of the productive model in Spain during the crisis - Miguel Torrejón-Velardiez (Ибероамериканские тетради)
This article establish relationships between the strong impact of crisis on the Spanish economy and the structural weaknesses of the growth model in the previous phase. Finally conclude about the need to promote speciﬁc economic policies to change that model as well as the forms of competition. However , it is found that the orientation of these policies has not driven this change, especially policies on R&D, which are speciﬁcally analyzed in this paper